Pengaruh Budaya Organisasi, Motivasi Kerja Terhadap Kepuasan Kerja Dengan Komitmen Organisasi Sebagai Variabel Intervening - Alfiani Triangga dewi (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose is: (1)To know the influence of the Significance of Organizational Culture on Organizational Commitment on the employees (2)the influence of the significance of work motivation to organizational commitment to employees, (3)the influence of organizational commitment to job satisfaction on employees, (4) significant influence of organizational culture on job satisfaction (5) significant influence of work motivation to job satisfaction, (6) influence of organizational culture, work motivation to job satisfaction, (7) influence organizational culture and work motivation to job satisfaction, (8) influence organizational culture, Work Motivation to Job Satisfaction with Organizational commitment as intervening variable. The type of this research is quantitative, population is 360 employees. Sampel used as 78 employees, with sampling motode using convience sampling with slovin formula. Data collection using questionnaires. The analysis technique used is multiple regression supported by T test. The result of analysis shows that organizational culture has no effect on organizational commitment, work motivation has significant effect to organizational commitment, organizational commitment have significant effect to job satisfaction, organizational culture has no effect to job satisfaction, organizational culture and work motivation collectively have an effect on job satisfaction, organizational culture, work motivation has no effect on job satisfaction with organizational commitment as intervening variable.